2021
DOI: 10.1016/j.jbc.2021.100443
|View full text |Cite
|
Sign up to set email alerts
|

Common allotypes of ER aminopeptidase 1 have substrate-dependent and highly variable enzymatic properties

Abstract: Polymorphic variation of immune system proteins can drive variability of individual immune responses. Endoplasmic reticulum aminopeptidase 1 (ERAP1) generates antigenic peptides for presentation by major histocompatibility complex class I molecules. Coding SNPs in ERAP1 have been associated with predisposition to inflammatory rheumatic disease and shown to affect functional properties of the enzyme, but the interplay between combinations of these SNPs as they exist in allotypes has not b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 56 publications
(108 reference statements)
3
41
2
Order By: Relevance
“…Allotype 10 was slightly less efficient, with 54-62% of peptide signal originating from product peptides. Still, this difference is much less pronounced than observed in previous in vitro experiments using single peptides that suggested that allotype 10 can be as much as 60-fold less active for some peptides 27 . This finding suggests that although allotype 10 may be less active for some substrates, it is still able to operate with good efficiency in complex substrate mixtures.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Allotype 10 was slightly less efficient, with 54-62% of peptide signal originating from product peptides. Still, this difference is much less pronounced than observed in previous in vitro experiments using single peptides that suggested that allotype 10 can be as much as 60-fold less active for some peptides 27 . This finding suggests that although allotype 10 may be less active for some substrates, it is still able to operate with good efficiency in complex substrate mixtures.…”
Section: Resultscontrasting
confidence: 59%
“…Some differences were, however, evident between ERAP1 allotypes. This was most activity as demonstrated before 27 . Still, allotype 10 was able to efficiently trim large peptide clusters suggesting that its lower activity may be sequence specific.…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…ERAP1 is also polymorphic, and coding single nucleotide polymorphisms (SNPs) in the ERAP1 gene associate with predisposition to autoimmunity or cancer often in epistasis with HLA alleles 24 and can help shape the cellular immunopeptidome 25 . ERAP1 SNPs are found in the population in limited combinations that define specific allotypes and have functional consequences in peptide trimming 26,27 . The exact interplay of ERAP1 and HLA polymorphic variation in determining antigen presentation is currently a subject of active research 21,[27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…ER aminopeptidase 1 (ERAP1) has been demonstrated to be crucial for the generation of many antigenic peptides and to be able to indirectly regulate adaptive immune responses by influencing the repertoire of antigenic peptides presented on the cell-surface, often referred to as the immunopeptidome 3 . ERAP1 is polymorphic and several common allotypes exist in the population affecting its functional properties and predisposition to disease such as cancer and autoimmunity 4 , 5 . Due to its important role in adaptive immune responses, ERAP1 is an emerging target for cancer immunotherapy and inflammatory diseases with autoimmune etiology 6 8 .…”
Section: Introductionmentioning
confidence: 99%